2000
DOI: 10.1021/jo991026f
|View full text |Cite
|
Sign up to set email alerts
|

Computational Explorations of Vinylcyclopropane−Cyclopentene Rearrangements and Competing Diradical Stereoisomerizations

Abstract: The rearrangements and stereoisomerizations of four systems, vinylcyclopropane, 4-tert-butylvinylcyclopropane, 5-methylvinylcyclopropane, and 2,5-dimethylvinylcyclopropane, as well as a variety of deuterated derivatives and 1- and 2-methyl-, methoxy-, difluoro-, and amino-substituted species, were studied by density functional theory calculations using the B3LYP functional and the 6-31G basis set. Energies were evaluated with CASSCF(4, 4)/6-31G single point calculations. The major product is obtained by the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
35
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 41 publications
6
35
0
Order By: Relevance
“…Both studies agree on the biradical nature of the rearrangement and on the preference for the si-stereochemistry of rearrangement suggested by the WoodwardÀHoffmann rules [3]. For the unsubstituted system, two more TSs, slightly (0.3 -1.1 kcal mol À1 ) higher in energy, were calculated; they were reached by motions deviating from the minimal-energy pathway [9]. These results suggest that dynamical calculations might be more suited for the description of the vinylcyclopropane !…”
supporting
confidence: 78%
“…Both studies agree on the biradical nature of the rearrangement and on the preference for the si-stereochemistry of rearrangement suggested by the WoodwardÀHoffmann rules [3]. For the unsubstituted system, two more TSs, slightly (0.3 -1.1 kcal mol À1 ) higher in energy, were calculated; they were reached by motions deviating from the minimal-energy pathway [9]. These results suggest that dynamical calculations might be more suited for the description of the vinylcyclopropane !…”
supporting
confidence: 78%
“…In 1997, Houk et al [15], as well as Davidson and Gajewski [16], reported on calculations of the vinylcyclopropane rearrangement by UB3LYP/6-31G*, confirmed by CAS-SCF(4,4) studies. A later extended version by Houk and co-workers included calculations of 2'-(tert-butyl)-and several methylated vinylcyclopropanes [17].…”
mentioning
confidence: 99%
“…Structures on this plane return to s-gauche-2 without a barrier. The mentioned TS is essentially pure diradical in character [17] and corresponds to the endo-allylic 3 in Scheme 1. Yet, the reaction is concerted, and the TS is located on the si pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…UB3LYP was chosen, since unrestricted density functional theory, in addition to its capability to accurately describe heterolytic bond cleavage, turns out to work exceptionally well also for diradicalic singlet states resulting from homolytic bond cleavage, at comparably low computational cost. 30,31 To relax putative strain due to the previously applied Hartree-Fock level, 200 fs free density functional QM/MM MD were performed before switching on the flooding potential.…”
Section: Setupmentioning
confidence: 99%